1973
DOI: 10.1159/000230989
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Migration Inhibition as an Indicator of Cellular Hypersensitivity to Soluble Antigens

Abstract: We evaluated delayed hypersensitivity in humans to three soluble an < tigens (tuberculoprotein, coccidioidin, and Candida extract) with the leukocyte migration inhibition test. Skin reactivity and migration inhibition correlated to a high degree with all the antigens. Cell migration was not inhibited in subjects without a positive skin test or clinical history. Sensitivity to tuberculin measured in vitro after vaccination with Bacillus of Calmette and Guerin correlated well with 25 tuberculin PPD skin test uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…c) higher doses than 80 ng/ml of PPD may be necessary to demonstrate Ml in birds showing a lower level of hypersensitivity. Rauch and King (1973) in a study of BCG vaccines showed that LMI correlated well with 25 tuberculin PPD skin test units or less, but did not detect less sensitive individuals who only responded to higher concentrations of antigen. As suggested by Rauch and King (1973) it is conceivable that persistence of live organisms in the lesions of birds (i. e.; group 2) bind sensitive lymphocytes thus reducing their numbers in the peripheral circulation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…c) higher doses than 80 ng/ml of PPD may be necessary to demonstrate Ml in birds showing a lower level of hypersensitivity. Rauch and King (1973) in a study of BCG vaccines showed that LMI correlated well with 25 tuberculin PPD skin test units or less, but did not detect less sensitive individuals who only responded to higher concentrations of antigen. As suggested by Rauch and King (1973) it is conceivable that persistence of live organisms in the lesions of birds (i. e.; group 2) bind sensitive lymphocytes thus reducing their numbers in the peripheral circulation.…”
Section: Discussionmentioning
confidence: 96%
“…Soborg and Bendixen (1967) showed that human peripheral leucocytes could also be used in the capillary tube technique, for demonstration of cellular hypersensitivity. This source of leucocytes was later used by Rauch and King (1973) in a direct leucocyte migration inhibition (LMI) test to evaluate delayed hypersensitivity in humans to 3 soluble antigens (tuberculo-protein, coccidiosidin and candida extract). They found a high degree of correlation between skin reactivity and Ml with all 3 antigens.…”
Section: Introductionmentioning
confidence: 99%
“…The LMI tests were undertaken as previous ly described [22]. White blood cells of patients and controls were separated from a blood sample by gravity sedimentation.…”
Section: Methodsmentioning
confidence: 99%
“…Since the presence of an immune response in patients to a specific viral isolate would indeed contribute support for, among other possibilities, the etiologic role of virus(es) in MS, the present experiments were designed to compare 6/94 and Sendai viruses as anti gens. Recognizing that tissue damage in MS may be cell-mediated, we tested patients and normal subjects for responsiveness to 6/94 and Sendai viruses using the leukocyte migration inhibition test (LMI) [22], an assay which has been established as an in vitro correlate of cellular hyper sensitivity to a variety of soluble and particulate antigens [23,24].…”
Section: Introductionmentioning
confidence: 99%